The Study of Managerial Knowledge, Attitude, and Intention Toward Willingness To Pay On Consumers Cosmetic Products - Ahmad Harianto, Raden; Rony, Zahara; Syarief, Faroman; Fauzi, Ahmad (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2023)
This study serves to test and analyze the effect of managerial knowledge, attitudes, and intentions on willingness to pay for cosmetic product consumers in Jakarta. This study uses a survey method and causality. So the samples obtained in this study were 201 respondents. The research method uses SEM analysis with the Warp PLS 7.0 program as a test tool. The results of this study are in Managerial Knowledge which has a very positive effect on Consumer Payment Intentions for Cosmetic Products significantly and Attitudes have a positive effect on Consumer Payment Intentions for Cosmetic Products significantly. This research has also shown that the intention to pay has a very significant positive effect on the willingness to pay to consumers. These tree main issues therefore should be taken into consideration in strategic planning that It is necessary to increase managerial knowledge by supporting attitudes and intentions through education and training programs to improve willingness to pay on consumers cosmetic products